2013
DOI: 10.1038/mp.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of MBD5 contributes to a spectrum of psychopathology and neurodevelopmental abnormalities

Abstract: Microdeletions of chromosomal region 2q23.1 that disrupt MBD5 contribute to a spectrum of neurodevelopmental phenotypes, however the impact of this locus in human psychopathology has not been described. To characterize the structural variation landscape of MBD5 disruptions and the associated psychopathology, 22 individuals with genomic disruption of MBD5 (translocation, point mutation, and deletion) were identified through whole-genome sequencing or cytogenomic microarray at 11 molecular diagnostic centers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 61 publications
(55 reference statements)
2
84
0
Order By: Relevance
“…Motor delays with poor coordination and broad-based/ataxic gait are seen in over 70% of individuals, 2,5,6 with the average age of walking 2-3 years of age. 2,6 Language development is severely impaired in individuals with 2q23.1 deletion syndrome.…”
Section: Developmental Delaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Motor delays with poor coordination and broad-based/ataxic gait are seen in over 70% of individuals, 2,5,6 with the average age of walking 2-3 years of age. 2,6 Language development is severely impaired in individuals with 2q23.1 deletion syndrome.…”
Section: Developmental Delaysmentioning
confidence: 99%
“…Motor delays with poor coordination and broad-based/ataxic gait are seen in over 70% of individuals, 2,5,6 with the average age of walking 2-3 years of age. 2,6 Language development is severely impaired in individuals with 2q23.1 deletion syndrome. Most reported pediatric cases either lack speech entirely 2 or have single words (2-3 word phrases), 5,7 and a few individuals speak 2-6 sentences.…”
Section: Developmental Delaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These sleep studies further support previous reports regarding del 2q23.1 patients' sleep habits. [4][5][6][7][8][9][10][11][12] Although this survey may reflect a subjective measure of the sleep phenotype present in 2q23.1 deletion syndrome patients as parents/guardians answered the survey, parents are in a unique position to describe their child's regular sleep behaviors. Importantly,~55.6% of parents reported that they use medication to improve the poor sleep patterns in their children, which is a significant indicator of the difficulties faced by the child and the family because of the sleep problems.…”
Section: Discussionmentioning
confidence: 99%
“…4 Sleep disturbance have been previously reported in a few cases. [4][5][6][7][8][9][10][11][12] Some of the sleep disturbances mentioned in these cases are waking 6-8 times per night, apparent night terrors in the early part of sleep, and waking in the early hours of the morning. [4][5][6][7][8][9][10][11][12] Although it is clear a sleep disturbance exists in del 2q23.1, no systematic characterization of the extent of sleep problems in this population has been published.…”
Section: Introductionmentioning
confidence: 99%